Imprints of primordial voids on the CMB - Baccigalupi, Carlo; Amendola, Luca; Occhionero, Franco (Arxiv, 2017)
We generalize in several ways the results existing in the literature: a) we make use of an exact general relativistic solution for a spherical, nearly empty cavity in the matter dominated era to evaluate the null geodesics and the Sachs-Wolfe effect; b) we evaluate the magnitude of the adiabatic fluctuations of the photon-baryon plasma; c) we study the influence of the shell profile; and d) we take into account the finite thickness of the last scattering surface (LSS) and the influence of its position with respect to the void center. We find empirically an analytic approximation to the Sachs-Wolfe effect for all crossing geometries and we derive an upper limit of $≈$ 25